GEN Y LEADER: QUALITATIVE PHENOMENOLOGY LEADERSHIP STUDIES IN PLN APD JATENG & DIY - Akmalaputri, Arsyadany Ghana; Yuniawan, Ahyar; Djastuti, Indi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2017)
This qualitative phenomenological study to examine and compare the style and character of Gen Y leadership with the style and character of Gen X leadership in PT. Perusahaan Listrik Negara Area Pengatur Distribusi Jawa Tengah & Daerah Istimewa Yogyakarta. The study was conducted through in-depth interviews and direct observation of selected respondents. The questions are (i) Gen X (old) leadership in preparing the cadre to deal with change, (ii) Gen Y's leadership in responding to the company's target challenge in the face of change.The respondents of this study were the group of Gen Y leaders and the group of Gen X leaders at PT. PLN APD Jateng & DIY. The method used is qualitative phenomenology. It is used because the purpose of this study to reveal the meaning of concept or phenomenon of experience based on the awareness that occurs in some individuals in PT. PLN APD Jateng & DIY.The results showed that Gen Y Leader at PT. PLN APD Jateng & DIY provides an understanding of organizational achievement targets to staff or subordinates in typical millennial youth. In addition to coaching, mentoring and counseling (CMC) and streamlining the WhatsApp Group (WA), they also often hang out together. The leadership cadre preparation process continues unabated, through an active WA Group 24 hours a day, seven days a week, and 30 days in a month. While the leaders of Gen X only use the CMC, code of conduct (CoC), and the person in charge (PIC) for the pattern of regeneration. The results also show that in addition to being very open to differences, Gen Y's leaders are also very tolerant of conflict in working relationships.